Brain‐derived neurotrophic factor and post‐stroke depression. Issue 3 (5th August 2019) - Zhang, Eric; Liao, Ping
Abstract: Brain‐derived neurotrophic factor (BDNF) is well known to play a critical role in cognition. Its role in mood disorders, including post stroke depression (PSD), is also recognized with more evidence surfacing. In patients with PSD, their serum BNDF level is lower than in those without depression. Furthermore, antidepressants could enhance BDNF expression in the brain, resulting in an alleviation of depression symptoms. Such therapeutic effect can be abolished in animals with the BDNF gene deleted. In PSD patients, the presence of stroke may contribute to the development of depression, including affecting the expression of BDNF. However, the mechanisms of BDNF in the development of PSD remain largely unknown. Lower BDNF levels may have existed in some patients before stroke onset, making them vulnerable to develop depressive symptoms. Meanwhile, the hypoxic environment induced by stroke could possibly downregulate BDNF expression in the brain. Current antidepressant treatments are not specific for PSD and there is a lack of treatments to address the linkage between stroke and PSD. This review summarizes the current knowledge of BDNF in PSD. By regulating BDNF expression, a synergistic effect may be achieved when such treatments are applied together with existing antidepressants.